Upregulation of CD1d and ULBP3 on B cells from healthy donors and chronic lymphocytic leukaemia patients does not prime them for killing by γδ T cells - Julie David; Amy Walsh; Ke Sin Seow; Ellen Walsh; Stefan Elekes; Rohit Upadhyay; Nawal A. B. Taher; Samiha Al Siyabi; Ashanty M. Melo; Carmel Waldron; Elisabeth Vandenberghe; Anthony M. McElligott; et al. (PLoS ONE, 2026)
Despite advances in treatment, chronic lymphocytic leukaemia (CLL) remains an incurable disease. Vδ1 + γδ T cells are reported to expand in CLL patients and to kill leukemic cells, placing them as candidates for immunotherapy. However, their cytotoxic efficacy was limited and required specific stimulatory conditions. Since some γδ T cells recognise lipids presented by CD1d, we examined if inducing CD1d expression and presentation of CD1d-restricted lipids could promote Vδ1, Vδ2 or Vδ3 T cell killing of B cells from CLL patients and healthy donors. Lines of γδ T cells containing Vδ1, Vδ2 and Vδ3 T cells and enriched cultures of CD19 + B cells were generated from peripheral blood using magnetic bead separation. γδ T cell subset frequencies and CD1d and ULBP3 expression levels on B cells were determined using flow cytometry. CD1d expression was induced on B cells by treatment with all trans retinoic acid (ATRA) and its analogue AM580. ATRA-treated B cells were co-cultured with γδ T cell lines in the absence or presence of lipids and cytotoxicity was assessed by measuring CD107a externalisation or propidium iodide staining using flow cytometry. Vδ1 and Vδ3 T cell frequencies were significantly higher in CLL patients compared to age-matched healthy donors. CD1d and ULBP3 expression was lower on CLL cells compared to healthy B cells but was restored by treatment with ATRA or AM580. Although co-culturing CLL cells with γδ T cells led to decreased cell viability, CD1d and ULBP3 upregulation by healthy and CLL B cells did not elicit cytolytic degranulation or cytokine production by Vδ1, Vδ2 or Vδ3 T cells, even after presentation of CD1d-restricted lipid antigens. This study suggests that human Vδ1 T cell cytotoxicity against CLL B cells may be disease stage-dependent and requires B cell priming and selective activation of specific γδ T cell subsets.